2021
DOI: 10.1002/celc.202100742
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Anode Compartment for Energy Efficient CO2 Reduction at Neutral pH

Abstract: Energy efficient CO 2 reduction in neutral pH requires the development of electrochemical devices operating with minimal energy input. To reach this objective, we propose an original approach focused on the anode compartment where the oxygen evolution reaction (OER) takes place. Different anode catalysts, anolytes and membranes were tested, and the components resulting in the most energy efficient and stable CO 2 reduction reaction device were selected. A stainless-steelbased anode with significant OER activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Ni foil, mesh, and foam modified by various methods like etching, laser ablation, , transition metal electrodeposition, and spray coating of nanoparticles, are commonly investigated as OER electrodes. Ni has already been employed as anode catalyst in recent studies on CO2RR. Concentrated electrolyte solutions (e.g., 1 M KOH) were used in most of these studies, and stability was mostly demonstrated in electrolyzer cells operating with liquid catholyte for relatively short time periods. High electrolyte concentration, however, leads to the formation of alkali metal carbonates/bicarbonates in the gas diffusion electrode (GDE) cathode, leading to the clogging of the gas channels and the concurrent selectivity decrease for CO2RR (with the simultaneous increase of the hydrogen evolution reaction (HER) rate). Ni foam has also been applied in non-zero-gap flow cells with a bipolar membrane or paired with a molecular catalyst for CO2RR. ,, Additionally, NiO nanoparticles were employed to oxidize 5-(hydroxymethyl)­furfural to 2,5-furandicarboxylic acid, paired with CO2RR .…”
Section: Comparing the Operation Of A Zero-gap Co2 Electrolyzer Cell ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ni foil, mesh, and foam modified by various methods like etching, laser ablation, , transition metal electrodeposition, and spray coating of nanoparticles, are commonly investigated as OER electrodes. Ni has already been employed as anode catalyst in recent studies on CO2RR. Concentrated electrolyte solutions (e.g., 1 M KOH) were used in most of these studies, and stability was mostly demonstrated in electrolyzer cells operating with liquid catholyte for relatively short time periods. High electrolyte concentration, however, leads to the formation of alkali metal carbonates/bicarbonates in the gas diffusion electrode (GDE) cathode, leading to the clogging of the gas channels and the concurrent selectivity decrease for CO2RR (with the simultaneous increase of the hydrogen evolution reaction (HER) rate). Ni foam has also been applied in non-zero-gap flow cells with a bipolar membrane or paired with a molecular catalyst for CO2RR. ,, Additionally, NiO nanoparticles were employed to oxidize 5-(hydroxymethyl)­furfural to 2,5-furandicarboxylic acid, paired with CO2RR .…”
Section: Comparing the Operation Of A Zero-gap Co2 Electrolyzer Cell ...mentioning
confidence: 99%
“…Ni has already been employed as anode catalyst in recent studies on CO2RR. 24 32 Concentrated electrolyte solutions (e.g., 1 M KOH) were used in most of these studies, and stability was mostly demonstrated in electrolyzer cells operating with liquid catholyte for relatively short time periods. High electrolyte concentration, however, leads to the formation of alkali metal carbonates/bicarbonates in the gas diffusion electrode (GDE) cathode, leading to the clogging of the gas channels and the concurrent selectivity decrease for CO2RR (with the simultaneous increase of the hydrogen evolution reaction (HER) rate).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a flow setup where electrolytes were recirculated in both anode and cathode compartments enabled minimisation of ohmic losses and efficient removal of bubbles produced at the surface of the electrodes. This work therefore focuses on studying novel OER catalysts not only in a static setup, but also in a flow setup closer to industrial operating conditions, where higher currents can be maintained for longer durations [37,38] . Elemental analysis of the electrolyte by inductively coupled mass spectroscopy (ICP‐MS) confirmed the absence of irreversible Ni and Fe dissolution over the course of the experiment, reflecting the high stability of the surface (Figure S6B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the average composition of the resulting material (66.2 % Fe, 22.5 % Ni and 11.3 % Cr) was very close to that of stainless steel (SS), which contains a minimum of 10.5 % of Cr, providing anti‐corrosion properties, and a minimum of 10 % of Ni. As SS is a trimetallic alloy containing transition metals that are known as active centres for OER catalysis (such as Ni and Fe) and since it is a cheap and widely available material, several authors, including ourselves, have considered it as an interesting potential OER catalyst [37,53–56] . The bottom‐up approach and multi‐parameter analysis of the Cr leaching phenomenon presented here enables a deeper understanding of the important characteristics of trimetallic NiFe‐based catalysts.…”
Section: Resultsmentioning
confidence: 99%